Labor force participation and retirement of older adults in Mexico during the Covid-19 pandemic - OROZCO ROCHA, KARINA (2022)
This paper examines labor force participation and retirement of older adults in Mexico during the Covid-19 pandemic, highlighting previous work characteristics. Workers in 2019 and retirees in 2020 are examined, using Heckman selection model; and data from the National Survey of Occupation and Employment of 2019 and 2020. Results indicate that men, younger cohorts, and residents in less urban localities are more likely to work in 2019. Of those workers in 2019, hose most likely to be retired in 2020 are: part-time workers and those in economic activities affected during the pandemic; social security and position in occupation were not statistically significant. In conclusion focused and differentiated actions are needed that contribute to the conservation of sources of labor income for the elderly during the prolonged pandemic.